Antigenic and genetic analysis of pandemic influenza A(H1N1) 2009 viruses from Portugal - Pechirra, Pedro (2010)
Backround: The influenza AH1N1 2009 pandemic virus (AH1N1pdm) was first detected in Portugal in May 4th 2009. This virus had origin in a reassortment between a North American swine lineage (already a triple reassortant, circulating in pigs since the late 1990’s) and a Eurasian swine lineage. As the HA (North American swine lineage) continues to circulate in the human population, its antigenic sites will continue to be targeted by antibody-mediated selection pressure. Therefore it is important from a public health perspective, continue to characterise the HA and to monitoring the antigenic and genetic properties of the AH1N1pdm viruses in order to detect any changes and thus any necessity for selecting further vaccine candidates or changes in antiviral recommendations. In this study, is presented a genetic and antigenic characterisation of influenza AH1N1pdm viruses, isolated in Portugal over the 2009 influenza pandemic. Material and Methods: In Portugal, during the 2009 influenza pandemic, about 16500 clinical samples were tested by the National Influenza Reference Laboratory for the presence of influenza AH1N1pdm virus. From near 8000 AH1N1pdm-positive samples, 147 were isolated in MDCK-SIAT1 cell cultures and characterised antigenically by hemagglutination-inhibition assays (HI). Of these, 56 isolates were taken for sequence analysis of the HA1 gene segment. Results: Antigenically, the AH1N1pdm viruses are homogeneous, being similar to A/California/7/2009 and the later pandemic H1N1 viruses A/Bayern/69/2009 and A/Lviv/N6/2009. However, 12 of the isolated viruses show 4-fold or greater reductions in the HI titre against most of the HI sera panel. They react better with sera raised against the A/Bayern/69/2009 and A/Lviv/N6/2009. Three of these isolated viruses presented amino acid substitutions at hemagglutinin antigenic sites (G155E in epitope B; R205K in epitope D and E258D in epitope E of the HA1 subunit) and in one strain was observed the amino acid substitution V199I in the vicinity of epitope D. Changes in positions 153-157 of the HA have been highly associated with reduced HI titers with ferret antisera to the A/California/7/2009 vaccine virus. These changes usually emerge after virus propagation in cell cultures. Sequenced hemagglutinins of portuguese isolates show that these viruses, with two exceptions, belong to the clade 7, already described in the literature. As known, viruses from this clade have a S203T mutation. One of our strains, A/Lisboa/31/2009, belongs to clade 6, as presents the Q293H amino acid change. This viral strain was isolated from a patient that arrived from the USA (Boston, New York) in June 2009. Another viral strain, A/Lisboa/35/2009, belongs to an earlier clade (at least, previous to clade 4) because it don’t presents the S203T neither the Q293H in its hemagglutinin and it lacks also the V106I and N248D amino acid changes in its neuraminidase. Additionally, mutations P83S in HA present in all the portuguese isolated viruses and I321V in the majority of them have been observed in all the non-clade 1 isolates. Conclusions: The great majority of influenza AH1N1pdm viruses isolated in Portugal were similar to the vaccine strain A/California/7/2009. They were representative of the clade 7, except two strains with foreign travel history. Most of the observed amino acid changes in the HA were located at antigenic sites or in their vicinity.